Feeding strategy of the jundiá Rhamdia quelen (Siluriformes, Heptapteridae) in costal lagoons of southern Brazil - DOI: 10.4025/actascibiolsci.v31i1.335 - Kutter, Mateus Tavares; Bemvenuti, Marlise de Azevedo; Moresco, Alex (Acta Scientiarum. Biological Sciences, 2009)
Feeding strategy and mouth morphology of ‘jundiá’ in costal lagoons of south of Rio Grande do Sul were studied. Gut contend of 189 individuals were collected from 2002 to 2004 and analysed according Amundsen. Fishes and crustaceans were the feeding items more frequent in the diet. Mollusk, insects and plants had low FO%. Season variation in diet showed lower variety of feeding items during summer and higher in winter. The diet vary according to site were irrigation channels showed low FO% for all items. The ‘jundiá’ showed generalist feeding strategy, generally preying on fish and crustaceous. On the description of its feeding apparatus the importance on the capture prey was observed.